Redescription of Mimon koepckeae (Chiroptera: Phyllostomidae) - Natalí Hurtado (Zoologia (Curitiba), 2014)
Mimon koepckeae Gardner & Patton, 1972 is a poorly-known bat species, with only three known specimens, including the holotype. Its distribution is restricted to the type locality in Ayacucho Department, Peru, and surroundings. This species has been synonymized with M. crenulatum by some authors. Based on a new specimen of M. koepckeae collected from Santuario Nacional Pampa Hermosa, Junin Department, Peru, we provide an extensive morphological comparison with M. crenulatum (Geoffroy St.-Hilaire, 1803), Mimom bennettii (Gray, 1838), and Mimon cozumelae Goldman, 1914, concluding that M. koepckeae is a valid species. As a result the distribution range of the species is extended 160 km north of the type locality. In addition, we characterize the habitat of the species, provide current data on feeding behavior, and suggest that M. koepckeae should be categorized as endangered species.